2020
DOI: 10.18203/issn.2454-2156.intjscirep20201271
|View full text |Cite
|
Sign up to set email alerts
|

Post-injection thrombophlebitis in patients undergoing peripheral IV catheterization in a tertiary care hospital: incidence and risk factors

Abstract: <p class="abstract"><strong>Background:</strong> Intravenous catheters cause endothelial damage and trauma, which can predispose to venous thrombosis. Peripheral vein infusion thrombophlebitis occurs in 25- 35% of hospitalized patients with intravenous catheters and has both patient-related implications (e.g., sepsis) and economic consequences (e.g., extra nursing time). This study is designed to address this issue, by assessing the potential risk factors in those who have developed phlebitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(34 reference statements)
2
1
0
Order By: Relevance
“…Among these, 53 participants developed thrombophlebitis which gives an incidence of 6.4%. [9] In study Dragana Simin for incidence, severity and risk factors of peripheral intravenous catheter-induced complications Phlebitis ranked first among complications with occurrence of 44%, followed by extravasation of 16.3%, while the incidence of occlusion and catheter dislodgement was 7.6% and 5.6%, respectively compare to this in our study (n=25) rate of phlebitis is 5(20%) ,rate of extravasation 6(24%) and catheter occlusion dysfunction 4(16%). [10] Conclusion : Our present study had concluded that there was significant difference between use of central venous catheter and peripheral intravenous catheter when life span of catheter and catheter related complications were compared the central venous catheter had more life span and less complications.…”
Section: Discussionsupporting
confidence: 47%
“…Among these, 53 participants developed thrombophlebitis which gives an incidence of 6.4%. [9] In study Dragana Simin for incidence, severity and risk factors of peripheral intravenous catheter-induced complications Phlebitis ranked first among complications with occurrence of 44%, followed by extravasation of 16.3%, while the incidence of occlusion and catheter dislodgement was 7.6% and 5.6%, respectively compare to this in our study (n=25) rate of phlebitis is 5(20%) ,rate of extravasation 6(24%) and catheter occlusion dysfunction 4(16%). [10] Conclusion : Our present study had concluded that there was significant difference between use of central venous catheter and peripheral intravenous catheter when life span of catheter and catheter related complications were compared the central venous catheter had more life span and less complications.…”
Section: Discussionsupporting
confidence: 47%
“…7 According to Rai et al an average time of IV cannulation was 5 days, with use of 20-gauge cannula for all patients. 8 The present study reported phlebitis incidence of 6.3% among 28850 PVCs observed. In the initial months (January, February and March) the incidence of phlebitis was high (9.89%,9.92% and 9.69 respectively).…”
Section: Discussionsupporting
confidence: 46%
“…Similar result of incidence of thrombophlebitis was reported by Rai et al, they also noted predominantly grade I phlebitis, followed by grade II and very few grades III. 8 In a study by Saji et al out of total 82 patients recruited 50% incidence of thrombophlebitis was reported. 6 61% of them were with grade 1 thrombophlebitis and remaining grade 2 was in 39% of patients without any incidence of grade 3 thrombophlebitis, with no association of thrombophlebitis incidence and risk factors considered.…”
Section: Discussionmentioning
confidence: 98%